DIGITAL TRANSFORMATION AND FIRM PERFORMANCE: THE ROLE OF TECHNICAL WORKFORCE CAPABILITY - VIJENDER SINGH (IJRDO - Journal of Business Management, 2026)
Digital transformation has become an important strategic mechanism through which firms seek to improve competitiveness, operational effectiveness, and performance. This study examined the relationship between digital transformation and firm performance while assessing the role of technical workforce capability. A quantitative explanatory research design was adopted using secondary firm-level data comprising 2,000 observations. Digital transformation was measured through a continuous transformation index, technical workforce capability was represented by the proportion of technical employees, and firm performance was primarily assessed through firm growth, with return on assets used for robustness analysis. Descriptive statistics, correlation analysis, multicollinearity diagnostics, hierarchical multiple regression, moderation analysis, and robustness tests were employed. The findings revealed that digital transformation had a statistically significant positive association with firm growth and remained positively associated with return on assets in the robustness analysis. Technical workforce capability, however, demonstrated a significant negative direct association with firm growth. Furthermore, its interaction with digital transformation was statistically insignificant, providing no evidence that technical workforce capability moderated the digital transformation-performance relationship. The findings indicate that digital transformation can contribute to improved firm performance, whereas merely increasing technical workforce concentration may not generate complementary performance benefits. Firms should therefore combine digital investments with effective workforce development, knowledge integration, and organizational learning practices.